2014
DOI: 10.1103/physrevlett.113.046102
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Atom Mobility on the Surface of a Metastable Film

Abstract: A remarkable enhancement of atomic diffusion is highlighted by scanning tunneling microscopy performed on ultrathin metastable body-centered tetragonal Co films grown on Fe(001). The films follow a nearly perfect layer-by-layer growth mode with a saturation island density strongly dependent on the layer on which the nucleation occurs, indicating a lowering of the diffusion barrier. Density functional theory calculations reveal that this phenomenon is driven by the increasing capability of the film to accommoda… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
25
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
4
4
1

Relationship

2
7

Authors

Journals

citations
Cited by 25 publications
(25 citation statements)
references
References 33 publications
0
25
0
Order By: Relevance
“…The QUAN-TUM ESPRESSO package [37] was used for the calculations, within plane waves and ultrasoft pseudopotentials. The Fe pseudopotential was generated starting from scalar-relativistic all-electron atomic calculations and using nonlinear core corrections, and has been extensively studied in our previous works [38][39][40]. We used a kinetic energy cutoff of 45 Ry for the wave functions and 200 Ry for the effective potential and the charge density.…”
Section: B Ab Initio Calculationsmentioning
confidence: 99%
“…The QUAN-TUM ESPRESSO package [37] was used for the calculations, within plane waves and ultrasoft pseudopotentials. The Fe pseudopotential was generated starting from scalar-relativistic all-electron atomic calculations and using nonlinear core corrections, and has been extensively studied in our previous works [38][39][40]. We used a kinetic energy cutoff of 45 Ry for the wave functions and 200 Ry for the effective potential and the charge density.…”
Section: B Ab Initio Calculationsmentioning
confidence: 99%
“…A 5 monolayers (ML) thick buffer layer of metallic Co was grown onto the Fe(001)-p(1 脳 1)O surface. In such a thickness range, Co is known to grow pseudomorphically on the Fe substrate [33,34], with a body centered tetragonal (bct) structure and the same inplane lattice parameter as bulk Fe (a Fe = 0.287 nm). The growth of thin Co films on Fe(001)-p(1 脳 1)O is known to proceed in a layer-by-layer (also known as Frank-van der Merwe) mode, as demonstrated by former studies [33,35] and confirmed by our STM observations [36].…”
Section: Experimental Methodsmentioning
confidence: 99%
“…8 Our recent contributions to the field range from the study of different AF materials, such as 3d metal oxides, 9 to the addition of controlled amounts of oxygen to the growth recipes of a large number of magnetic heterostructures. [10][11][12][13] Regardless of its actual composition (either Fe or Cr), the presence of a passivating layer of oxygen induces deep modifications in the structural equilibrium of the surface, which usually relaxes by increasing the distance between the topmost layer and the subsurface ones.…”
Section: Introductionmentioning
confidence: 99%